2021
DOI: 10.17582/journal.aavs/2021/9.5.722.733
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal Activity of Some Medicinal Plant Extracts against Different Developmental Stages of the Camel Tick Hyalomma dromedarii

Abstract: H yalomma dromedarii (Acari: Ixodidae) is considered the most common tick species infesting camels in Africa, Asia, and the Middle East. The adverse economic impact of H. dromedarii ticks comes from irritation, annoyance, anemia, secondary skin infection, tick fever, and is considered as a vector for various devastating diseases (Abdel-Shafy et al., 2012; Abdullah et al., 2016; Yadav et al., 2017).Eco-friendly control of ticks is currently a crucial challenge (Benelli et al., 2016; Khater et al., 2016) where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Approximately, 300 larvae (for each concentration) were immersed for 1 min in 1 ml of the tested concentrations (4, 8, 16, and 32 mg/ml) of the synthesized ZnO NPs according to the method described by Abdel-Ghany et al . [ 30 ]. Each concentration was replicated 3 times (100 larvae/replicate).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately, 300 larvae (for each concentration) were immersed for 1 min in 1 ml of the tested concentrations (4, 8, 16, and 32 mg/ml) of the synthesized ZnO NPs according to the method described by Abdel-Ghany et al . [ 30 ]. Each concentration was replicated 3 times (100 larvae/replicate).…”
Section: Methodsmentioning
confidence: 99%
“…A similar spectrum was observed previously. [ 51 ] The FTIR spectrum for the AgNPs shows the main characteristic band of the Artemisia extract with a low shift, which indicates that the main functional group works as a reducing and capping agent.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the use of herbal medications becomes a promising alternative approach for the treatment of various infectious agents because of their biodegradability, target efficiency, and cost-effectiveness, and therefore, they gained a considerable interest in tropical and subtropical regions (18)(19)(20)(21)(22)(23)(24)(25)(26). Among others, plant-derived materials and their bioactive substances were proposed as substitutes for synthetic acaricides due to their activity against ticks (27). As compared to synthetic ones, several previous reports revealed that herbal acaricides caused little environmental pollution and a low toxicity level to non-target organisms including humans, apart from the rapid biodegradation of their residues and their role in prevention of resistance development (28,29).…”
Section: Introductionmentioning
confidence: 99%